Literature Review: Peran Sosial Media terhadap Perkembangan Strategi Komunikasi Pemasaran Produk - Venka Eldwina Lestariolita (Universitas Batanghari, 2022)
Social media has become a new force in communication, even today social media plays an important role as a force for companies around the world to build brands and markets. The method used in this research is a literature review study. Where the literature included in this article was obtained from the Google Scholar site, where the researcher found 18 literatures relevant to the topic raised by the researcher, of which there were 2 international literature and 16 national literatures. The conclusion of this study is based on the results and discussion above, it can be concluded that social media plays an important role in developing communication strategies for product marketing. Many studies state that social media increases sales because they often use social media as a communication strategy with consumers. However, there are several studies which state that the success of a company is not only measured by its marketing communication strategy, but from all strategies implemented by business people. Efforts must be made by companies to use social media as a product communication strategy so that the role of social media can be realized by all companies, both small and large.